A critical interpretive synthesis of migrants' experiences of the Australian health system - Kimberly Lakin; Sumit Kane (BMC, 2023)
Abstract While the health of and healthcare use by migrants has received significant scholarly and policy attention in Australia, current debates highlight that a critical examination of the theoretical underpinnings of these inquiries and responses is needed. We conducted a systematic review and critical interpretive synthesis (CIS) to critically examine how the policy and scholarly literature conceptualises migrants' interactions with and experiences of the Australian health system. Guided by PRISMA, we searched for literature without imposing any limits. We also searched key State and Federal Government websites for relevant policy documents. Our initially broad inclusion criteria became refined as the CIS progressed. We prioritised the likely relevance and theoretical contribution of the papers to our inquiry over methodological quality. The CIS of 104 papers revealed that the Australian scholarly literature and policy documents consistently homogenise and reduce migrants according to an assumed, (1) cultural identity, (2) linguistic affiliation, and/or (3) broad geographic origin. Based on these three critiques and drawing on the theoretical literature, we propose a synthesising argument on how the Australian literature could better conceptualise migrants' experiences of the Australian health system. We contend that both research and policy should explicitly recognise and engage with the multifaceted and shifting ways that migrants define themselves, generally, and during their encounters with destination country health systems. Engagement with this notion is necessary for also understanding how aspects of migrants' identities are dynamically co-constructed during their interactions with the health system. These understandings have implications for improving the design and implementation of policies and programs directed at improving the responsiveness of Australia's health system to the needs and expectations of migrant communities specifically, and destination countries broadly.